Manipulating human dendritic cell phenotype and function with targeted porous silicon nanoparticles. (February 2018) - Stead, Sebastian O.; McInnes, Steven J.P.; Kireta, Svjetlana; Rose, Peter D.; Jesudason, Shilpanjali; Rojas-Canales, Darling; Warther, David; Cunin, Frédérique; Durand, Jean-Olivier; Drogemuller, Christopher J.; Carroll, Robert P.; Coates, P. Toby; et al.
Abstract: Dendritic cells (DC) are the most potent antigen-presenting cells and are fundamental for the establishment of transplant tolerance. The Dendritic Cell-Specific Intracellular adhesion molecule-3-Grabbing Non-integrin (DC-SIGN; CD209) receptor provides a target for dendritic cell therapy. Biodegradable and high-surface area porous silicon (pSi) nanoparticles displaying anti-DC-SIGN antibodies and loaded with the immunosuppressant rapamycin (Sirolimus) serve as a fit-for-purpose platform to target and modify DC. Here, we describe the fabrication of rapamycin-loaded DC-SIGN displaying pSi nanoparticles, the uptake efficiency into DC and the extent of nanoparticle-induced modulation of phenotype and function. DC-SIGN antibody displaying pSi nanoparticles favourably targeted and were phagocytosed by monocyte-derived and myeloid DC in whole human blood in a time- and dose-dependent manner. DC preconditioning with rapamycin-loaded nanoparticles, resulted in a maturation resistant phenotype and significantly suppressed allogeneic T-cell proliferation.